MANAGING CENTRIFUGAL PUMP RELIABILITY IN THE CONTEXT OF TOTAL COST OF OWNERSHIP - Van der Poel, J.; Van Waveren, C.C. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The management of a population of centrifugal pumps in the petrochemical industry can be daunting. A popular method for strategically optimizing the maintenance and operation of these centrifugal pumps is to measure the reliability of the whole pump population in terms of Mean-Time-Between-Failures (MTBF). Too often MTBF improvement becomes the focus rather than a means of supporting the actual goal, namely Total Cost of Ownership (TCO) reduction. An increase in MTBF is intuitively associated with a reduction of TCO, but this is not necessarily true. This study proposes that the